2011
DOI: 10.4028/www.scientific.net/amr.264-265.1538
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Powder Synthesis Method on the Sinterability of Hydroxyapatite

Abstract: The sinterability of hydroxyapatite (HA) powder synthesized through a novel wet chemical method (HAp) and a wet mechanochemical method (HAwm) was investigated over a temperature range of 1000oC to 1400oC in terms of phase stability, bulk density, hardness and fracture toughness. The results indicated that the sinterability of HAp powder were significantly better than HAwm powder. Moreover, the XRD traces of HAwm sintered samples showed signs of decomposition into TTCP when sintered at 1300oC and above. Densifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…For this reason CHA-S disk has higher hardness value than BHA-S sample. Literature has reported that hardness (HV) value of dense HA is between 3.0 GPa and 7.0 GPa [11]. The hardness of ceramics depends on grain size and porosity, however some researchers reported that increase of the surface area changes hardness values of ceramic materials.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason CHA-S disk has higher hardness value than BHA-S sample. Literature has reported that hardness (HV) value of dense HA is between 3.0 GPa and 7.0 GPa [11]. The hardness of ceramics depends on grain size and porosity, however some researchers reported that increase of the surface area changes hardness values of ceramic materials.…”
Section: Resultsmentioning
confidence: 99%